Complementary Feeding Innovation from Soybean and Dragon Fruit Peel Enhances Macro- and Micronutrient Biomarkers in Malnourished Rats - Rauf Muhammad Abdul; Arinda Lironika; Zora Olivi; Agatha Widiyawati (ARTERI : Jurnal Ilmu Kesehatan, 2026)
Malnutrition remains a major public health concern characterized by deficiencies in both macronutrients and micronutrients. The use of locally based functional foods such as soybean (Glycine max) and dragon fruit peel (Hylocereus polyrhizus) offers potential as an alternative nutritional intervention. This study aimed to evaluate the effect of soybean and dragon fruit peel-based complementary feeding (MP-ASI) formulation on total protein, albumin, and zinc levels in a malnutrition rat model. This experimental study employed a pre–posttest randomized controlled group design involving 15 male Sprague Dawley rats divided into three groups (KN, KP, and P). Malnutrition was induced using a 5% low-protein diet for 21 days, followed by intervention with the MP-ASI formula at a dose of 2.4 g/day/200 g BW. Parameters measured included weekly body weight, serum total protein, albumin, and zinc levels before and after the intervention. Data were analyzed using one-way ANOVA Tukey's post hoc test, and paired t-test. The results demonstrated marked improvements in nutritional biomarkers following the intervention, with total protein increasing from 1.13 to 6.88 g/dL, albumin from 1.53 to 4.53 g/dL, and zinc from 0.67 to 1.34 g/dL (all p = 0.001). In contrast, no significant improvement was observed in the malnutrition control group. The combination of soybean and dragon fruit peel in MP-ASI formulations has the potential to improve protein, albumin, and zinc levels under malnutrition conditions and may serve as a promising locally based nutritional intervention strategy.